Myocardial infarction with non-obstructive coronary artery disease, a retrospective cohort study: Are plaque disruption and other pathophysiological mechanisms the same disease? - Asıl, Serkan; Barış, Veysel Özgür; Geneş, Muhammet; Taşkan, Hatice; Görmel, Suat; Yıldırım, Erkan; Gökoğlan, Yalçın; Çelık, Murat; Yüksel, Uygar Çağdaş; Kabul, Hasan Kutsi; Barçın, Cem (Journal of Surgery and Medicine, 2021)
Backgound/Aim: Myocardial infarction with non-obstructive coronary arteries (MINOCA) is an increasingly recognized entity. Recent studies have shown that MINOCA is not a benign syndrome, with younger MINOCA patients having outcomes comparable to their myocardial infarction with obstructive coronary artery disease (MI-CAD) counterparts. In this study, we will describe the demographic, clinical and angiographic characteristics of MINOCA patients in our hospital. Methods: In this retrospective cohort study, all patients who underwent coronary angiography with the diagnosis of acute coronary syndrome during September 2016-April 2019 were screened and those with MINOCA were detected. We described the demographic, clinical, and angiographic characteristics of MINOCA patients and compared the etiologic and pathophysiological mechanisms. Results: A total of 3855 patients with acute coronary syndrome were screened and 155 were diagnosed with MINOCA, with a total prevalence of 4.02%. Among them, 48.4% were female and the overall mean age was 55.04 (13.57) years. Plaque disruption was the most common cause of MINOCA (48.4%), which was followed by microvascular dysfunction and slow flow (9.7%). We compared plaque disruption and other causes to find that age (58.31 (13.76) vs 51.89 (12.68) P=0.003), hypertension (37 (48.7%) vs 25 (31.6%) P=0.034), prior coronary artery disease history (16 (21.1%) vs 2 (2.5%) P=0.001) and creatinine clearance (67.35 (IQR: 25.8) vs 74.0 (IQR: 28.58) P=0.009) were higher in patients with plaque disruption than those without. Conclusion: MINOCA is a diagnosis of exclusion with numerous potential causes. The etiological and pathophysiological mechanisms of plaque disruption are different from other causes of MINOCA and the correct treatment approach determines the prognosis.